Strategi Dinas Koperasi dalam Pembinaan Kelembagaan Koperasi Mewujudkan Kemandirian Ekonomi - Sulis Dewi Astutik; Angguliyah Rizki A (Indonesian Journal Publisher, 2025)
This study describes the cooperative institutional development strategies implemented by the Department of Cooperatives and Micro Enterprises of Malang Regency to promote members’ economic independence. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation, then analyzed using Miles and Huberman’s interactive model. Findings indicate three main strategies: managerial training to enhance professionalism, digitalization assistance to improve efficiency and transparency, and regular monitoring and evaluation to ensure sustainability. These strategies effectively improved governance and member participation, although challenges remain in rural cooperatives with limited internet access and human resource capacity. The study highlights the need for adaptive, technology-based development for modern and independent cooperatives.